A web-based solution for robotic telepresence. (12th December 2017) - Melendez-Fernandez, Francisco; Galindo, Cipriano; Gonzalez-Jimenez, Javier
Robotic telepresence is an emerging technology with a great potential in applications such as elder assistance, telework, and surveillance. It relies on a combination of information and communication technologies and mobile robotics to provide a person with autonomy to move and interact in a remote environment. The application environments range from homes to factories, even large outdoor spaces, and the type of users involved in particular application contexts is also varied. That leads to a great heterogeneity in the design of the robotic platforms, communication infrastructures, and interfaces found across robotic telepresence applications. This article analyzes the sources of such heterogeneity, defines a modular architecture that provides a suitable solution for generic applications, and presents an instantiation of the architecture into a web-based solution for robotic telepresence. The main advantages of the solution presented are its open-source nature and its cross-platform compatibility. We report a pilot experience that shows how a functional robotic telepresence system based on this solution has been successfully deployed in an office environment and intensively tested by inexperienced participants over the Internet.